Analisis Hubungan Asosiasi Antara Indeks Prestasi Kumulatif (IPK) Dengan Kegiatan Organisasi Mahasiswa di Universitas Sultan Ageng Tirtayasa - Jeri Irawan; Alya Nurul Ryzkyani; Raditya Ahnaf Fauzan; Aniq Juman Ramadhani; Mutiah Mutiah (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
GPA reflects the quality of one's academic achievement in college and is often used as a measure of academic success. This study was conducted to find out more about the effect of organizational activities followed by students on the average GPA achieved. The research population only includes active students of Sultan Ageng Tirtayasa University. In this study, the sample used amounted to 50 students studying at Sultan Ageng Tirtayasa University. The data collection technique used is a survey method using Google Form as the main tool and distributed through social networks such as WhatsApp groups. The research method includes several stages: Identify research variables, collect data and test the relationship between the two research variables. The results showed that at the 5% significance level there was no relationship between student GPA and student participation in organizations. Students do not need to worry because the Cumulative Performance Index (GPA) and student organization activities at Sultan Ageng Tirtayasa University are not valid. Because according to this study, if you join an organization, your cumulative grade point average (GPA) is always good and above average.